1989
DOI: 10.1080/02652038909373801
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal uptake and immunological effects of carrageenan—current concepts

Abstract: Carrageenans are a group of high molecular weight sulphated polygalactans which find extensive use in the food industry as thickening, gelling and protein-suspending agents. Although there is no evidence to suggest that the persorption of small amounts of carrageenans across the intestinal barrier poses an acute toxic hazard, they are known to be biologically active in a number of physiological systems and extended oral administration in laboratory animals has been shown to modify both in vivo and in vitro imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Although the European Commission of Scientific Committee on Food stated that food-grade carrageenin is safe to use [2,3] , some earlier evidence from animal studies has demonstrated that degraded carrageenin, with a molecular weight of ^ 30,000, causes ulcerations and malignancies in the gastrointestinal tract [4] and affects incidence of mammary carcinoma [5] . Carrageenin, which can in limited amounts pass through intestinal barrier in experimental animals, may be harmless in healthy organisms, but it may become toxic in groups with disorders of the gastrointestinal tract [1] . The adverse effects of poligeenan (a product of acid hydrolysis in stomach) are ulcerations of intestinal mucosa [6][7][8] , or stimulating neoplastic effect [9] .…”
mentioning
confidence: 99%
“…Although the European Commission of Scientific Committee on Food stated that food-grade carrageenin is safe to use [2,3] , some earlier evidence from animal studies has demonstrated that degraded carrageenin, with a molecular weight of ^ 30,000, causes ulcerations and malignancies in the gastrointestinal tract [4] and affects incidence of mammary carcinoma [5] . Carrageenin, which can in limited amounts pass through intestinal barrier in experimental animals, may be harmless in healthy organisms, but it may become toxic in groups with disorders of the gastrointestinal tract [1] . The adverse effects of poligeenan (a product of acid hydrolysis in stomach) are ulcerations of intestinal mucosa [6][7][8] , or stimulating neoplastic effect [9] .…”
mentioning
confidence: 99%
“…The tight junctions between the intestinal epithelial cells provide an efficient barrier to absorption of macromolecules, including food-grade carrageenans [13]. Uptake of macromolecules can occur via the macrophages of the gut-associated lymphoid tissue [13,21]. The presence of carrageenan in the macrophages or epithelial cells of the gut-associated lymphoid tissue is consistent with the normal process of antigen sampling by the gastrointestinal tract [11,21].…”
Section: Immune System Toxicitymentioning
confidence: 74%
“…Some of the effects of systemic administration include acronecrosis, nephrotoxicity, hepatotoxicity, increased spleen weight, hematological changes and storage of carrageenan in the liver, kidney and macrophages (see 2,33,34). Intraperitoneal administration of carrageenan to laboratory animals at sufficient doses may produce reduced primary antibody responses to T-cell dependent antigens (see 21). Whether carrageenan administered orally has effects on the immune system is the subject of intense research.…”
Section: Immune System Toxicitymentioning
confidence: 98%
“…Carrageenan (CAR) is a sulphated polygalactose extracted from red seaweeds, Chrondrus crispus, Gigartina stellata and various Euchema species (Nicklin and Miller, 1989). Currently, CAR is widely used in the food industry as a thickening, gelling, stabilizing and/or proteinsuspending agent.…”
Section: Introductionmentioning
confidence: 99%
“…Those include suppression of antibody production, cellular immunity, and delayed-type hypersensitivity and elongation of graft survival (Thomson and Fowler, 1981;Kolb et al, 1981). Additionally, CARtreatment led macrophages to release two contradictory immunoregulat ory mediators in vitro, interleukin-1 and prostaglandin (Nicklin and Miller, 1989).…”
Section: Introductionmentioning
confidence: 99%